The relationship of training and morale to productivity of work members of Paspampres in Group A - Dito Herrys Dika Putra; Fendy Suhariadi; Sri Pantja Madyawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Work productivity is the ability of a labor in production compared to the input used, a workforce can be said to be productive when able to produce goods or services in accordance with the expected in the time right. The purpose of this research is to find out and analyze the influence of training on the work productivity of Paspampres members in Group A and to find out and analyze the influence of work morale on the work productivity of Paspampres members in Group A and to know and analyze the influence of training and morale together. on the work productivity of Paspampres members in Group A.This research method using correlation to see how big the influence of free variables and bound variables. Multiple Regression Analysis Testing the hypothesis in this study using multiple regression analysis. The population of this research are members of Paspampres at Group A which amounted to 535 people and made the sample in this study as many as 84 people. Each respondent is given questions using Likert scale. From the results of this study obtained as follows: 1) Training affects the work productivity of Paspampres Members in Group A, training will also increase the work productivity of Paspampres Members in Group A; 2) Work enthusiasm affects the work productivity of Paspampres Members in Group A, the higher the work spirit, the higher the work productivity of Paspampres Members in Group A; 3) Training and work spirit affect the work productivity of Paspampres members in Group A, increasing training and working spirit together will increase the work productivity of Paspampres members in Group A. Regarding the y variable for members of the Paspampres group because work productivity is low, it is certain that the security of VVIP will be threatened. This research is only limited to the effect of training and morale on the work productivity of Paspampres members in Group A. In the future, research needs to be carried out with objects or organizations that are different from those currently being studied. In this case, the research that the author is researching has never been done on the military in Indonesia, which always gives good performance results under conditions under pressure that always remains enthusiastic and productive in carrying out work duties.